2015
DOI: 10.1097/ta.0000000000000642
|View full text |Cite
|
Sign up to set email alerts
|

Nonpowder firearms cause significant pediatric injuries

Abstract: Epidemiologic study, level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…BBs, pellets, airsoft ammunition, International Journal of Orthopaedics nail guns). Most pediatric firearm injuries are due to powder weapons; however, non-powder weapons should not be discounted due to their potential for causing serious injury [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…BBs, pellets, airsoft ammunition, International Journal of Orthopaedics nail guns). Most pediatric firearm injuries are due to powder weapons; however, non-powder weapons should not be discounted due to their potential for causing serious injury [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Nationally, there were 21,840 injuries attributed to nonpowder toy guns in 2000 with significant reported morbidity . 20 These nonpowder guns may cause considerable morbidity as Veenstra et al 21 reported that 43.8% of patients with nonpowder firearm injuries required operative intervention. While handguns were the most common gun used overall, they were also the most common type of gun involved in accidental shootings, as children may mistake a real handgun for a toy.…”
Section: Discussionmentioning
confidence: 99%
“…Non-powder firearms such as pellet gun, air rifles, ball-bearing guns, paintball guns, are significant sources of injury and death among children and adolescents. The injury can involve the brain, eyes, head, neck, chest, abdomen, and extremities [ 1 ] [ 2 ]. Non-powder firearms have a velocity ranging from 80 to 300m/s and can cause injury up to 20-60 feet away.…”
Section: Introductionmentioning
confidence: 99%
“…Non-powder firearms have a velocity ranging from 80 to 300m/s and can cause injury up to 20-60 feet away. Pellets have several designs such as wad cutter, round nose, sharp-pointed, and hollow point [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation